Stripe disorder and dynamics in the hole-doped antiferromagnetic insulator La5/3Sr1/3CoO4 - Lancaster, T; Giblin, SR; Allodi, G; Bordignon, S; Mazzani, M; De Renzi, R; Freeman, P; Baker, P; Pratt, F; Babkevich, P; Blundell, S; Boothroyd, A; et al. (2014)
We investigate the magnetic ordering and dynamics of the stripe phase of La5/3Sr1/3CoO4, a material shown to have an hourglass magnetic excitation spectrum. A combination of muon-spin relaxation, nuclear magnetic resonance, and magnetic susceptibility measurements strongly suggest that the physics is determined by a partially disordered configuration of charge and spin stripes whose frustrated magnetic degrees of freedom are dynamic at high temperature and which undergo an ordering transition around 35 K with coexisting dynamics that freeze out in a glassy manner as the temperature is further reduced. © 2014 American Physical Society.